Holding the line [large type] - Delamere, Jennifer (Delamere, Jennifer. Love along the wires, 2023)
"A widow at just 30 years of age, Rose Finlay is determined to put all ideas of marriage and family behind her and pursue an independent life. But when she notices a young woman about to be led astray by a roguish aristocrat, bitter memories from her past arise, and she feels compelled to intervene. The unintended consequences of her efforts will ultimately force Rose to reexamine her life in a new light. As the overseer of his two widowed sisters' financial and domestic affairs, John Milburn carries heavy responsibilities for a single man. But he's faced with his biggest challenge when his headstrong niece falls prey to the attentions of a powerful man who could ruin both her and her family. When Rose and John join forces to protect his niece, they put everything they hold dear--including their growing attraction--in jeopardy"--